2011
DOI: 10.1537/ase.100903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anthropometric measures and socio-demographic factors on menstrual pain and irregular menstrual cycles among university students in Bangladesh

Abstract: Menstrual disturbances generally affect the daily activities of young females. The aim of this study was to determine the effects of anthropometric measures and sociodemographic factors on menstrual disturbances among university students in Bangladesh. Data were collected from 995 students from Rajshahi University using a stratified sampling technique between July 2004 and May 2005. Factors influencing menstrual pain and irregular menstrual cycles were examined with multiple logistic regression analysis. Stepw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
2
7
3
3
Order By: Relevance
“…As regards present of premenstrual syndrome, the majority of girls (82.8%) had premenstrual syndrome, while (56.8%) of them had physical symptoms as (colic-back pain-headache and exhaustion); less than half (43.6%) had moderate severity of premenstrual symptoms. As well as there was statistical difference between the severity of premenstrual symptoms of adolescent girls and their body mass index" BMI" (P= 0.007).Results similar to these current study findings were also reported in a study in Hossain et al 2011& Kavitha.2014 (27,28 ) the majority (72.30%) of the girls have premenstrual symptoms. Furthermore, and in agreement with these present study findings (29) reported that premenstrual symptoms were significantly more common among girls who were overweight, and did not do regular physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…As regards present of premenstrual syndrome, the majority of girls (82.8%) had premenstrual syndrome, while (56.8%) of them had physical symptoms as (colic-back pain-headache and exhaustion); less than half (43.6%) had moderate severity of premenstrual symptoms. As well as there was statistical difference between the severity of premenstrual symptoms of adolescent girls and their body mass index" BMI" (P= 0.007).Results similar to these current study findings were also reported in a study in Hossain et al 2011& Kavitha.2014 (27,28 ) the majority (72.30%) of the girls have premenstrual symptoms. Furthermore, and in agreement with these present study findings (29) reported that premenstrual symptoms were significantly more common among girls who were overweight, and did not do regular physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…The present study shows a significant (p<0.05) negative association between age at menarche and menstrual irregularities, indicating that girls who reached menarche earlier had a higher probability of experiencing irregular menstrual cycles. This is in converse with the findings of Hossain et al (2011). The coefficient of multiple logistic regression shows that MUAC and WHR have a significant negative association with menstrual irregularities.…”
Section: Discussioncontrasting
confidence: 52%
“…This finding is similar with the findings of Wei et al (2009) among the Australian women, where both overall BMI and obesity were significantly associated with irregular menstrual cycles. Hossain et al (2011), also reported a positive association (p<0.05) between BMI and irregular menstrual cycle. The present study shows a significant (p<0.05) negative association between age at menarche and menstrual irregularities, indicating that girls who reached menarche earlier had a higher probability of experiencing irregular menstrual cycles.…”
Section: Discussionmentioning
confidence: 80%
“…The range of menarcheal age was from 9 to 19 years, and more than 63% of female students reached menarche at between 12 and 13 years of age. Amongst the less developed countries, age of menarche appears to be later than in Malaysian females: in Indonesia, 12.96 years (Batubara et al, 2010); in Bangladesh, 13.12 years (Hossain et al, 2011); in Nigeria, 12.9 years (Lawan et al, 2010) and in Ethiopia, 15.8 years (Zegeye et al, 2009). A study on Malaysian adolescent females living in Negeri Sembilan, Malaysia, reported their average menarcheal age to be 12.3 years (Lee et al, 2006), close to the value of 12.5 years found for adolescent females in the USA by Anderson et al (2003).…”
Section: Discussionmentioning
confidence: 99%